A Stakeholder-Centric Exploration of Architectural Design Values and Decision-Making - dian nafi (JURNAL ARSITEKTUR PENDAPA, 2024)
This paper explores the intricate dynamics of architectural design, focusing on the delicate interplay between aesthetics and utility. Acknowledging the divergent priorities of architects, who often emphasize aesthetics, and the public, who prioritize utilitarian aspects, the study aims to navigate a balanced approach. The research is grounded in the recognition of individual stakeholder values as pivotal in shaping a comprehensive value system for optimal architectural service delivery. The overarching research question seeks to understand how architects can harmonize business and technical requirements to create designs that meet diverse stakeholder needs. Employing a qualitative research methodology, the study emphasizes the importance of recognizing, negotiating, and aligning values among stakeholders. By delving into the perspectives of architects, clients, and the broader public, the research seeks to establish a framework for decision-making that goes beyond subjective preferences. Additionally, the paper explores the quantification of benefits and the modeling of customer value as analytical tools in choosing between various system architectures. Findings reveal that a value-driven decision-making process, informed by data and inclusive of stakeholder perspectives, leads to architectures that not only satisfy aesthetic preferences but also serve practical, strategic, and societal objectives. The study contributes to a more nuanced understanding of the multifaceted nature of architectural design, emphasizing the importance of a holistic, stakeholder-centric, and data-informed approach